Manganese dioxide nano-enzyme loaded double-layer hemostatic sponge as well as preparation method and application thereof

By compounding modified chitosan with polyethylene glycol and sodium carboxymethylcellulose, and loading manganese dioxide nanozyme, a double-layer hemostatic sponge with high liquid absorption capacity, good mechanical properties, antioxidant and antibacterial functions was prepared , which solves the deficiencies of existing hemostatic sponges in terms of liquid absorption and mechanical properties, and effectively copes with the problems of active oxygen accumulation and bacterial growth on bleeding wounds.

CN119326940APending Publication Date: 2025-01-21JIANGNAN UNIV

Patent Information

Application Number
CN202411288631.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing hemostatic sponges have shortcomings in liquid absorption capacity and mechanical properties, and it is difficult to solve the problems of reactive oxygen accumulation and bacterial growth on bleeding wounds at the same time.

Method used

By compounding the modified chitosan and polyethylene glycol and carboxymethyl cellulose, and loading manganese nanoenase to prepare a double -layer hemostatic sponge of manganese nanoenase. Manganese dioxide nanobase has the ability to catalyze H2O2 into O2, which can alleviate oxidative stress and hypoxia, and has the effect of inhibiting bacterial growth.

Benefits of technology

This double -layer hemostatic sponge not only improves the absorption ability and mechanical performance of the liquid, shorten the in vitro coagulation time, but also has antioxidant and antibacterial functions, which can effectively remove active oxygen and inhibit bacterial growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326940A_ABST
    Figure CN119326940A_ABST
Patent Text Reader

Abstract

The invention relates to manganese dioxide nano-enzyme loaded double-layer hemostatic sponge as well as a preparation method and application thereof, and belongs to the technical field of biomedical materials. The double-layer hemostatic sponge comprises manganese dioxide nano-enzyme, catechol-based chitosan, a carboxyl-containing polymer and polyethylene glycol, the manganese dioxide nano-enzyme and a catechol-based chitosan solution are mixed to obtain a precursor, the precursor solution is subjected to pre-freezing forming, carboxymethyl cellulose and polyethylene glycol are subjected to crosslinking, and the double-layer hemostatic sponge is obtained. Dispersing the manganese dioxide nano-enzyme solution into the cross-linking solution, compounding the mixed solution with the pre-frozen and formed freezing liquid, freezing, and freeze-drying to obtain the double-layer hemostatic sponge. The prepared hemostatic sponge can continuously release the manganese dioxide nano enzyme, has good rapid hemostatic and mechanical properties, can absorb a large amount of blood, and can reduce active oxygen, bacteria and the like bred on a wound, so that the rapid hemostatic effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials, and specifically relates to a double-layer hemostatic sponge loaded with manganese dioxide nanoenzyme, and a preparation method and application thereof. Background Art

[0002] Massive bleeding is one of the main causes of casualties in war, traffic accidents, surgery and other traumatic events, accounting for more than 80% of preventable deaths. If hemostasis is not carried out in a timely and effective manner, excessive bleeding will occur, causing infection, leading to serious consequences such as coma, shock and even death. Therefore, the development of effective hemostatic materials to manage massive bleeding is an inevitable choice and has important significance in the field of biomedicine.

[0003] Hemostatic sponges are fine, porous, positively charged hemostatic materials. The porous structure of hemostatic sponges enables them to absorb large amounts of blood fluid while also concentrating coagulation components. Once they come into contact with blood, hemostatic sponges cause platelet adhesion and aggregation, which in turn promotes platelet plug formation and blocks blood flow from the wound. They also trigger the release of coagulation-related factors in the intrinsic and extrinsic coagulation pathways, thereby forming a stable clot that helps control wound bleeding. Therefore, sponge materials show great potential in bleeding control.

[0004] Patent (CN105944138A) discloses the preparation of a biodegradable medical polyurethane chitosan composite hemostatic sponge, but the use of a large amount of solvent results in poor safety of the sponge; Patent with publication number CN113577368A discloses a carboxylated chitosan medical sponge and its preparation method, but its liquid absorption capacity and other aspects still need to be improved; and the hemostatic sponges prepared by many patents have single performance and cannot solve the complex environmental problems of active oxygen accumulation and bacterial growth in bleeding wounds while stopping bleeding. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a double-layer hemostatic sponge loaded with manganese dioxide nanozyme and its preparation method and application. Modified chitosan is compounded with polyethylene glycol and sodium carboxymethyl cellulose, and manganese dioxide nanozyme is loaded at the same time. Manganese dioxide nanozyme is a typical nanozyme with good hemostatic performance, catalytic activity and stability, and can catalyze H 2 O 2 Decompose into O 2 , thereby alleviating oxidative stress and hypoxia. Manganese dioxide nanozymes also have a certain effect of inhibiting bacterial growth. Not only can it stop bleeding quickly, but it can also improve the mechanical support of the material, improve the wound microenvironment, reduce inflammation and fight bacteria, and other functions. It is expected to provide a new idea for the development and use of clinical products.

[0006] The present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a double-layer hemostatic sponge loaded with manganese dioxide nanozyme, comprising the following steps:

[0008] S1, preparing a manganese dioxide nanozyme dispersion and a catechol-based chitosan solution;

[0009] S2, dissolving the carboxyl-containing polymer and polyethylene glycol in deionized water, adding a cross-linking agent for cross-linking, and drying to obtain a cross-linked solution; the solute of the cross-linked solution is the carboxyl-containing polymer-polyethylene glycol;

[0010] S3, mixing the obtained manganese dioxide nanozyme dispersion with the obtained catechol-based chitosan solution and the obtained cross-linked solution, respectively, and freeze-drying to obtain a catechol-based chitosan layer loaded with manganese dioxide nanozyme and a cross-linked layer loaded with manganese dioxide nanozyme;

[0011] S4, laminating the catechol-based chitosan layer loaded with manganese dioxide nanozyme and the cross-linked layer loaded with manganese dioxide nanozyme obtained in step S3 to obtain the double-layer hemostatic sponge loaded with manganese dioxide nanozyme.

[0012] In one embodiment of the present invention, in step S1, the catechol-based chitosan solution is prepared by:

[0013] 3,4-dihydroxybenzaldehyde is dissolved in a mixed solution of deionized water and alcohol, then mixed with a chitosan acid solution, glacial acetic acid is added to promote dissolution, and reacted under nitrogen protection; sodium borohydride is added to the resulting post-reaction solution, and stirred at a high speed until no bubbles are generated, thereby obtaining the catecholized chitosan solution.

[0014] In one embodiment of the present invention, the mass ratio of chitosan to 3,4-dihydroxybenzaldehyde is 1:0.4 to 1:1.8.

[0015] In one embodiment of the present invention, in step S1, the particle size of the manganese dioxide nanozyme in the manganese dioxide nanozyme dispersion is 100 nm to 300 nm.

[0016] In one embodiment of the present invention, in step S2, the carboxyl-containing polymer is selected from one or more of sodium carboxymethyl cellulose, hyaluronic acid, silk fibroin, xanthan gum, methacrylate gelatin, chitosan, carboxymethyl cellulose, polyethylene glycol diacrylate, sodium alginate, polylactic acid, hyaluronic acid, polyvinyl pyrrolidone, polydopamine and polyvinyl alcohol.

[0017] In one embodiment of the present invention, in step S2, the mass ratio of the carboxyl-containing polymer to the polyethylene glycol is 4:1 to 9:1.

[0018] In one embodiment of the present invention, in step S2, the cross-linking agent is selected from one or more of citric acid, sodium citrate and glutaric acid; citric acid has both carbonyl and hydroxyl structures, and can form non-electrostatic hydrogen bond binding forces with the carbonyl of cellulose and the hydroxyl of polyethylene glycol; any substance having both functional groups can be substituted;

[0019] And / or, the mass concentration of the cross-linking agent is 10% to 20%;

[0020] And / or, the cross-linking time is 20 min to 30 min.

[0021] In one embodiment of the present invention, in step S3, the mass ratio of manganese dioxide nanozyme to catechol chitosan in the catechol chitosan layer loaded with manganese dioxide nanozyme is 2:1 to 2:5;

[0022] And / or, the mass ratio of manganese dioxide nanozyme to carboxyl-containing polymer-polyethylene glycol in the cross-linked layer loaded with manganese dioxide nanozyme is 2:1 to 2:5.

[0023] In one embodiment of the present invention, in step S4, the mass ratio of the catechol-based chitosan layer loaded with manganese dioxide nanozyme to the cross-linked layer loaded with manganese dioxide nanozyme is 5:1 to 1:1.

[0024] The second object of the present invention is to provide a double-layer hemostatic sponge loaded with manganese dioxide nanozyme prepared by the preparation method.

[0025] The thickness of the double-layer hemostatic sponge is 1 cm to 2 cm.

[0026] The third object of the present invention is to provide the use of the double-layer hemostatic sponge loaded with manganese dioxide nanozyme in the preparation of hemostatic products.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention provides a double-layer hemostatic sponge loaded with manganese dioxide nanozyme and its preparation method and application. The aldehyde group of 3,4-dihydroxybenzaldehyde and the amino group in chitosan undergo Schiff base reaction to obtain the chitosan, and the introduction of catechol groups improves the liquid absorption capacity of chitosan, and the cross-linking compound with sodium carboxymethyl cellulose-polyethylene glycol improves the mechanical support capacity of the sponge.

[0029] (2) The addition of manganese dioxide nanozymes not only shortens the in vitro coagulation time and increases the blood absorption rate, but also absorbs more red blood cells and platelets to promote coagulation. At the same time, the antioxidant and antibacterial functions of manganese dioxide nanozymes can reduce the accumulation of active oxygen and bacterial growth in the bleeding environment.

[0030] (3) The double-layer hemostatic sponge loaded with manganese dioxide nanozyme provided by the present invention not only greatly improves the liquid absorption capacity, but also has good mechanical properties, shortens the in vitro coagulation time, and also has antioxidant and antibacterial functions, removes active oxygen and inhibits bacterial growth. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0032] Figure 1 Schematic diagram of the preparation of the hemostatic sponge loaded with manganese dioxide nanozyme of the present invention;

[0033] Figure 2 This is a particle size distribution diagram of the manganese dioxide nanozyme of the present invention;

[0034] Figure 3 Figure 1 is an outline diagram of CCS, CCP and CCPM in the present invention;

[0035] Figure 4 The liquid absorption capacity of the sponge in Test Example 1 of the present invention; wherein A is the liquid absorption capacity of the hemostatic sponge in water; B is the liquid absorption capacity of the hemostatic sponge in anticoagulated whole blood;

[0036] Figure 5 The mechanical ability of the sponge in Test Example 2 of the present invention;

[0037] Figure 6 The absorption of blood components by the sponge in Test Example 3 of the present invention and the SEM image; wherein A is the absorption of platelets; B is the absorption of red blood cells; C is the SEM image of platelets and red blood cells on the sponge;

[0038] Figure 7 The extracorporeal hemostatic ability of the sponge in Test Example 4 of the present invention;

[0039] Figure 8 The antibacterial and antioxidant properties of the sponge in Test Example 5 of the present invention; wherein A is the antioxidant property of the hemostatic sponge; B and C are the antibacterial properties of the hemostatic sponge against Escherichia coli and Staphylococcus aureus, respectively;

[0040] Fig. 9 This is the in vitro biocompatibility of the sponge in Test Example 6 of the present invention. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0042] To achieve the above object, the present invention provides a method for preparing a hemostatic sponge loaded with manganese dioxide nanozyme, characterized in that it comprises the following steps:

[0043] S1, preparing a manganese dioxide nanozyme dispersion and a catechol-based chitosan solution;

[0044] S2, adding the carboxyl-containing polymer and polyethylene glycol into deionized water, stirring until completely dissolved, adding a cross-linking agent for cross-linking, and drying to remove water to obtain a cross-linked solution; the solute is the carboxyl-containing polymer-polyethylene glycol;

[0045] S3, mixing the manganese dioxide nanozyme dispersion with the catechol-based chitosan solution and the cross-linked solution, respectively, freezing, and then freeze-drying to obtain a catechol-based chitosan layer loaded with manganese dioxide nanozyme and a cross-linked layer loaded with manganese dioxide nanozyme;

[0046] S4. The catechol-based chitosan layer loaded with manganese dioxide nanozyme obtained in step S3 and the cross-linked layer loaded with manganese dioxide nanozyme are laminated to obtain a double-layer hemostatic sponge loaded with manganese dioxide nanozyme; the double-layer sponge not only greatly improves the liquid absorption capacity, but also has good mechanical properties, shortens the in vitro coagulation time, and also has antioxidant and antibacterial functions, removes reactive oxygen and inhibits bacterial growth.

[0047] Optionally, in S1, the preparation method of the catechol-based chitosan solution is as follows: dissolve chitosan in an acetic acid solution, dissolve 3,4-dihydroxybenzaldehyde in a mixed solution of deionized water and methanol, then mix with the chitosan solution, add glacial acetic acid to promote dissolution, and react under nitrogen protection. Sodium borohydride is added to the solution after the reaction, stirred at high speed until no bubbles are generated, the solution is filtered, and the precipitate is dissolved in a hydrochloric acid solution. Finally, dialyze in hydrochloric acid, dialyze in acetic acid, and dialyze in deionized water to obtain a catechol-based chitosan solution.

[0048] Optionally, in S1, the ratio of chitosan to 3,4-dihydroxybenzaldehyde is 1:0.4 to 1:1.8; preferably 1:0.4, 1:0.8, 1:1.2, 1:1.6, 1:1.8.

[0049] Optionally, in S2, the carboxyl-containing polymer is selected from one or more of sodium carboxymethyl cellulose, hyaluronic acid, silk fibroin, xanthan gum, methacrylate gelatin, chitosan, carboxymethyl cellulose, polyethylene glycol diacrylate, sodium alginate, polylactic acid, hyaluronic acid, polyvinyl pyrrolidone, polydopamine, and polyvinyl alcohol; preferably sodium carboxymethyl cellulose, and the ratio of sodium carboxymethyl cellulose to polyethylene glycol is 4:1 to 9:1.

[0050] Optionally, in S2, the mass concentration of the cross-linking agent is 10% to 20%, and the cross-linking time is 20 to 30 minutes.

[0051] Optionally, the ratio of the manganese dioxide nanozyme to catechol-based chitosan is 2:1 to 2:5; preferably 2:1, 2:2, 2:3, 2:4, 2:5; the ratio of the manganese dioxide nanozyme to sodium carboxymethyl cellulose-polyethylene glycol is 2:1 to 2:5; preferably 2:1, 2:2, 2:3, 2:4, 2:5.

[0052] Optionally, the mass ratio of the catechol-based chitosan layer loaded with manganese dioxide nanozyme to the cross-linked layer loaded with manganese dioxide nanozyme is 5:1 to 1:1; preferably 5:1, 4:1, 3:1, 2:1, 1:1.

[0053] Optionally, the method prepares a double-layer hemostatic sponge loaded with manganese dioxide nanozyme.

[0054] Optionally, the double-layer hemostatic sponge loaded with manganese dioxide nanozyme is used in the preparation of biological hemostasis.

[0055] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0056] In the embodiments of the present invention, CCS is catechol chitosan; CCP is a double-layer hemostatic sponge prepared by catechol chitosan / sodium carboxymethyl cellulose-polyethylene glycol; CCPM is a double-layer hemostatic sponge prepared by catechol chitosan / sodium carboxymethyl cellulose-polyethylene glycol loaded with manganese dioxide nanozyme.

[0057] Example 1: Preparation of hemostatic sponge loaded with manganese dioxide nanozyme

[0058] This embodiment provides a method for preparing a hemostatic sponge loaded with manganese dioxide nanozyme (flow chart as shown in Figure 1 As shown), comprising the following steps:

[0059] (1) Preparation of manganese dioxide nanozyme dispersion: distilled water (24.0 mL), sodium dodecylbenzene sulfonate (0.5 mol / L -1 , 1.6 mL), sulfuric acid solution (0.1 mol / L, 0.16 mL) and ethanol (99%, 3.2 mL) were mixed together and then heated to 90°C for 15 minutes. KMnO 4 The solution (0.05 mol / L, 0.32 mL) was reacted for 30 minutes to obtain MnO 2 Nanosheets, namely MnO 2 Nanozyme. The obtained MnO 2 The nanosheets were rinsed three times with deionized water. Finally, the obtained MnO 2Nanozyme (concentration 0.1 mg / mL) was diluted with water to obtain 0.2 mg / mL MnO 2 Nanozyme dispersion for further use.

[0060] The particle size distribution of the prepared manganese dioxide nanozyme dispersion is as follows: Figure 2 As shown by Figure 2 It can be seen that the particle size of the manganese dioxide nanozyme dispersion is mainly concentrated around 120 nm, and the difference in particle size distribution at different concentrations is small, indicating that the prepared manganese dioxide nanozyme dispersion is relatively stable.

[0061] (2) Preparation of catechol-based chitosan solution (CCS): Chitosan was dissolved in acetic acid solution, 3,4-dihydroxybenzaldehyde was dissolved in a mixed solution of deionized water and methanol, and then mixed with the chitosan solution, glacial acetic acid was added to promote dissolution, and the reaction was carried out under nitrogen protection for 3.5 hours. Sodium borohydride was added to the solution after the reaction, and it was stirred at high speed until no bubbles were generated. The solution was filtered and the precipitate was dissolved in hydrochloric acid solution. Finally, it was dialyzed in hydrochloric acid for 6 hours, in acetic acid for 2 hours, and in deionized water for 24 hours to obtain a catechol-based chitosan solution with a concentration of about 10%.

[0062] (3) Sodium carboxymethyl cellulose and polyethylene glycol are added to deionized water, stirred until completely dissolved, citric acid is added for cross-linking for 20 minutes, and dried at 40° C. for 24 hours to remove moisture to obtain a sodium carboxymethyl cellulose cross-linked polyethylene glycol solution with a concentration of 2%. The obtained sodium carboxymethyl cellulose cross-linked polyethylene glycol solution is freeze-dried to obtain CMC-PEG.

[0063] (4) mixing the manganese dioxide nanozyme dispersion with the catechol-based chitosan solution and the sodium methylcellulose cross-linked polyethylene glycol solution respectively to obtain a mixed solution of manganese dioxide nanozyme and catechol-based chitosan and a mixed solution of manganese dioxide nanozyme and sodium carboxymethylcellulose cross-linked polyethylene glycol; freezing at -80°C, and then freeze-drying to obtain a catechol-based chitosan layer loaded with manganese dioxide nanozyme and a sodium carboxymethylcellulose cross-linked polyethylene glycol layer loaded with manganese dioxide nanozyme; and laminating the two layers together to obtain a double-layer hemostatic sponge (CCPM) loaded with manganese dioxide nanozyme, wherein the CCPM is as follows: Figure 3 As shown, CCS is obtained by direct freeze-drying of a catechol-based chitosan solution.

[0064] Comparative Example

[0065] This comparative example prepared a catechol-based chitosan / sodium carboxymethyl cellulose-polyethylene glycol composite double-layer hemostatic sponge (CCP, such as Figure 3 The method is similar to that in Example 1, except that no manganese dioxide nanozyme is added.

[0066] Test Example 1: Liquid Absorption Capacity

[0067] To evaluate the absorption capacity of the sponge system in water and anticoagulated blood, take a certain mass of hemostatic sponge (CCPM and CCP) at room temperature, place it in water or anticoagulated whole blood for a period of time, and then take it out and weigh it. The calculation formula for liquid absorption rate is: liquid absorption rate = (W2-W1) / W1×100%, where W1 and W2 are the weight of the sample before and after immersion. Figure 4 As shown, A is the liquid absorption capacity of the hemostatic sponge in water; B is the liquid absorption capacity of the hemostatic sponge in anticoagulated whole blood; Figure 4 It can be seen that the double-layer hemostatic sponge loaded with manganese dioxide nanozyme prepared in the embodiment of the present invention exhibits excellent anticoagulant whole blood absorption capacity, which is beneficial to blood coagulation. Since manganese dioxide will occupy certain pores of the sponge and manganese dioxide does not absorb water, the water absorption rate of CCPM will be slightly lower than that of CCP.

[0068] Test Example 2: Sponge Mechanical Capability

[0069] The sponges of the embodiment and the comparative example were made into regular cylindrical shapes, soaked in distilled water for 3 minutes before testing to achieve swelling equilibrium, and then placed between the compression molds of a universal testing machine. The sponges were compressed to 50% of their original height at a speed of 1 mm / min, and the compression stress at 50% strain was recorded. The testing machine was restored to its original state, and the operation was repeated three times. Figure 5 As shown, the sponge has good mechanical properties.

[0070] Example 3: Absorption of blood components by sponge

[0071] (1) Platelet adhesion: Platelet-rich plasma was diluted with PBS, and the sponge was incubated with 500 μL of plasma at 37°C for 0.5 h. The sample was taken out and washed three times with PBS. The adhered platelets were lysed with lysis buffer for 1 h. Finally, the LDH value of the supernatant was determined using an LDH kit (purchased from Shanghai Yuanye Biotechnology Co., Ltd., R21833-50T). The results are as follows Figure 6 As shown in A, it can be seen that the hemostatic sponge has more than 50% adsorption of platelets, and the effect of CCPM hemostatic sponge is 20% higher than that of CCP hemostatic sponge.

[0072] (2) Red blood cell adhesion: Take blood cell-rich plasma, dilute it with PBS, incubate the sponge with 500 μL red blood cell suspension at 37°C for 0.5 h, and then measure the OD with a microplate reader. 540 The results are as follows Figure 6 As shown in B, it can be seen that the adsorption of red blood cells by both hemostatic sponges exceeds 50% after 10 minutes, and the adsorption effect of CCPM hemostatic sponge in 10 minutes to 20 minutes is better than that of CCP hemostatic sponge.

[0073] (3) The incubated sponges were fixed with glutaraldehyde for 2 h, and then dehydrated with 50%, 60%, 70%, 80%, 90%, and 100% ethanol solutions, respectively. After air drying, the differences in adsorption of platelets and red blood cells on the sponges were observed by SEM. Figure 6 As shown in C, it can be seen that the adsorption amount of CCPM hemostatic sponge is greater than that of CCP hemostatic sponge.

[0074] Test Example 4: Extracorporeal hemostasis ability of sponges

[0075] In the embodiment and the comparative example, 10 mg of sponge was mixed with 2 mL of anticoagulated whole blood, and then 60 μL of 0.2 M calcium chloride solution was added. The mixture was incubated at 37°C, and the fluidity was observed every 15 seconds to determine whether the blood was coagulated. Each experiment was repeated three times to obtain the average value. Figure 7 It can be seen that the double-layer composite hemostatic sponge loaded with manganese dioxide nanozyme greatly shortens the in vitro coagulation time.

[0076] Test Example 5: Antibacterial and Antioxidant Properties of Sponges

[0077] (1) The hemostatic sponge extract prepared in Example 1 was diluted to three concentrations of 50 μg / mL, 100 μg / mL, and 200 μg / mL, and mixed with 600 μL PBS, 200 μL H 2 O 2 The mixture was placed in a 37°C constant temperature oscillator for shaking, and 100 μL of samples were taken at 0, 5 min, 10 min, 20 min, 30 min, 60 min, 120 min, and 180 min, respectively. After centrifugation, 50 μL was taken and mixed with titanium sulfate solution, and the H 2 O 2 Absorbance value. Figure 8 It can be seen from A in that the hemostatic sponge prepared in the example has good antioxidant function.

[0078] (2) 30 μL of Escherichia coli and Staphylococcus aureus were inoculated into 100 mL of LB medium until the logarithmic growth phase. The sponge sterilized overnight by UV was mixed with 1 mL of bacterial solution and incubated at 37°C in a shaking incubator for 1 h. The OD600 was measured with an ELISA reader. The results are shown in Table 1. Figure 8 As shown in B and C in the figure, it can be seen that the hemostatic sponge prepared in the embodiment has good antibacterial function.

[0079] Test Example 6: In vitro biocompatibility

[0080] Wash CCS, CMC-PEG and CCPM and sterilize them. Soak them in DMEM high-glucose medium (purchased from Gibco, C11995500BT) for 24 hours to obtain a series of sponge extracts of different concentrations (0, 6.25μg / mL, 12.5μg / mL, 25μg / mL, 50μg / mL, 100μg / mL, 200μg / mL). Take 100μL of cell suspension and inoculate it in a 96-well plate. After the cells adhere to the wall, remove the medium, add 100μL of extract to the experimental group and 100μL of DMEM high-glucose medium to the control group. Culture them together for 24 hours. After discarding the original solution, add 100μL of MTT solution to each well and continue incubating for 4 hours. Aspirate the supernatant, add 100μL of DMSO solution to each well, and store in the dark for 15 minutes. Measure the absorbance at 570nm on an enzyme reader. Repeat three times. Fig. 9 As shown, the hemostatic sponge has no obvious cytotoxicity and exhibits good biocompatibility.

[0081] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a double-layer hemostatic sponge loaded with manganese dioxide nanozyme, characterized in that: The following steps are involved: S1, preparing a manganese dioxide nanozyme dispersion and a catechol-based chitosan solution; S2, dissolving the carboxyl-containing polymer and polyethylene glycol in deionized water, adding a crosslinking agent for crosslinking, and drying to obtain a crosslinked solution; S3, mixing the obtained manganese dioxide nanozyme dispersion with the obtained catechol-based chitosan solution and the obtained cross-linked solution, respectively, and freeze-drying to obtain a catechol-based chitosan layer loaded with manganese dioxide nanozyme and a cross-linked layer loaded with manganese dioxide nanozyme; S4, laminating the catechol-based chitosan layer loaded with manganese dioxide nanozyme and the cross-linked layer loaded with manganese dioxide nanozyme obtained in step S3 to obtain the double-layer hemostatic sponge loaded with manganese dioxide nanozyme.

2. The preparation method according to claim 1, characterized in that: In step S1, the catechol-based chitosan solution is prepared by the following method: 3,4-dihydroxybenzaldehyde is dissolved in a mixed solution of deionized water and alcohol, then mixed with a chitosan acid solution, glacial acetic acid is added to promote dissolution, and reacted under nitrogen protection; sodium borohydride is added to the resulting post-reaction solution, and stirred at a high speed until no bubbles are generated, thereby obtaining the catecholized chitosan solution.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the chitosan to 3,4-dihydroxybenzaldehyde is 1:0.4 to 1:1.

8.

4. The preparation method according to claim 1, characterized in that: In step S1, the particle size of the manganese dioxide nanozyme in the manganese dioxide nanozyme dispersion is 100 nm to 300 nm.

5. The preparation method according to claim 1, characterized in that: In step S2, the carboxyl-containing polymer is selected from one or more of sodium carboxymethyl cellulose, hyaluronic acid, silk fibroin, xanthan gum, methacrylate gelatin, chitosan, carboxymethyl cellulose, polyethylene glycol diacrylate, sodium alginate, polylactic acid, hyaluronic acid, polyvinyl pyrrolidone, polydopamine and polyvinyl alcohol.

6. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the carboxyl-containing polymer to the polyethylene glycol is 4:1 to 9:

1.

7. The preparation method according to claim 1, characterized in that: In step S2, the cross-linking agent is selected from one or more of citric acid, sodium citrate and glutaric acid; And / or, the mass concentration of the cross-linking agent is 10% to 20%; And / or, the cross-linking time is 20 min to 30 min.

8. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the catechol-based chitosan layer loaded with manganese dioxide nanozyme to the cross-linked layer loaded with manganese dioxide nanozyme is 5:1 to 1:

1.

9. A double-layer hemostatic sponge loaded with manganese dioxide nanozyme prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the double-layer hemostatic sponge loaded with manganese dioxide nanozyme according to claim 9 in the preparation of hemostatic products.

Citation Information

Patent Citations

  • Preparation method of biodegradable medical polyurethane and chitosan composite hemostatic sponge

    CN105944138A

  • Carboxylated chitosan medical sponge and preparation method thereof

    CN113577368A

Cited By

  • Multilayer composite hemostatic material and preparation method thereof

    CN120550177A